Governance Reforms In Indian Banking Sector: The Impact of Financial Sector Liberalization on Governance Reforms in the Indian Banking Sector (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Strengtheningfinancial systems has been one of the central issues facing emerging marketsand developing economies.   This isbecause sound financial systems serve as an important channel for achievingeconomic growth through the mobilization of financial savings,  putting them to productive use and transforming various risks (Beck,  Levin and Loayza 1999;  King and Levin 1993;  Rajan andZingales 1998;  Demirgüç-Kunt, Asli  and Maksimovic  1998;  Jayaratne and  Strahan  1996). Many countries adopted a series offinancial sector liberalization measures in the late 1980s and early 1990s thatincluded interest rate liberalization, entry deregulations, reduction ofreserve requirements and removal of credit allocation. In many cases, thetiming of financial sector liberalization coincided with that of capitalaccount liberalization. Domestic banks were given access to cheap loans fromabroad and allocated those resources to domestic production sectors.